2017
DOI: 10.1371/journal.pgen.1006814
|View full text |Cite
|
Sign up to set email alerts
|

MoCAP proteins regulated by MoArk1-mediated phosphorylation coordinate endocytosis and actin dynamics to govern development and virulence of Magnaporthe oryzae

Abstract: Actin organization is a conserved cellular process that regulates the growth and development of eukaryotic cells. It also governs the virulence process of pathogenic fungi, such as the rice blast fungus Magnaporthe oryzae, with mechanisms not yet fully understood. In a previous study, we found that actin-regulating kinase MoArk1 displays conserved functions important in endocytosis and actin organization, and MoArk1 is required for maintaining the growth and full virulence of M. oryzae. To understand how MoArk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 66 publications
2
55
1
Order By: Relevance
“…Previously, studies in M. oryzae showed that the nuclear division is critical in appressorium function (Marroquin‐Guzman et al ., ). To further understand whether the deletion of MoPPE1 caused a nuclear division defect that may account for restricted invasion, a histone H1 protein fused to a red fluorescent protein (H1‐RFP) construct was introduced into the wild‐type strain and Δ Moppe1 mutant (Li et al ., ,b; Marroquin‐Guzman et al ., ). However, the nuclear number were of no significant difference between the Δ Moppe1 mutant and the wild‐type strains at 0, 4, 12, 24 h and infection phase when observed, suggesting that MoPpe1 may be dispensable for nuclear division which was in coordination with cell growth (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, studies in M. oryzae showed that the nuclear division is critical in appressorium function (Marroquin‐Guzman et al ., ). To further understand whether the deletion of MoPPE1 caused a nuclear division defect that may account for restricted invasion, a histone H1 protein fused to a red fluorescent protein (H1‐RFP) construct was introduced into the wild‐type strain and Δ Moppe1 mutant (Li et al ., ,b; Marroquin‐Guzman et al ., ). However, the nuclear number were of no significant difference between the Δ Moppe1 mutant and the wild‐type strains at 0, 4, 12, 24 h and infection phase when observed, suggesting that MoPpe1 may be dispensable for nuclear division which was in coordination with cell growth (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The GFP‐MoNut1 fusion construct was introduced into Δ Moppe1 and Δ Monut1 mutants respectively. The proteins extracted from mycelium were resolved on 8% SDS‐polyacrylamide gels prepared with 50 μM acrylamide‐dependent Phos‐tagligand and 100 μM MnCl 2 as described (Li et al ., ,b). Gel electrophoresis was run at 60 V for 6 ± 8 h. Prior to transfer, gels were equilibrated in transfer buffer containing 5 mM EDTA for 30 min two times and then in transfer buffer without EDTA for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…graminearum have been verified to be involved in endocytosis and pathogenicity (Dou et al ., ; Zhang et al ., ). Through functional analysis of endocytic proteins such as the ArfGAP protein MoGlo3 (Zhang et al ., ), the class V myosin MoMyo5 (Tang et al ., ), the capping protein MoCap (Li et al ., ), the verprolin protein MoVrp1 (Huang et al ., ), the ADP‐ribosylation factor Arf6 (Zhu et al ., ), the actin‐regulating kinase homologue MoArk1 (Wang et al ., ) and an early endocytic protein‐MoEnd3 (Li et al ., ), it was revealed that endocytosis is essential for conidiogenesis, appressorium formation and pathogenicity in P . oryzae .…”
Section: Discussionmentioning
confidence: 97%
“…The recombination plasmid was isolated using the Yeast Plasmid Mini Preparation Kit (Sangon Biotech, SK1246, Shanghai, China), and plasmids containing the correct inserts were transformed into protoplasts of M. oryzae , as previously described (Yang et al ., ). The CDS of MoHMT1 was cloned and ligated into the pYF11 vector (L. Li et al ., ) to produce the MoHMT1‐GFP fusion construct (primers shown in Table S1), driven by its 1.5 kb native promoter, and was subsequently transformed into the MoHMT1 ko mutant strain. The transformed strain was selected by bleomycin resistance on OA plates.…”
Section: Methodsmentioning
confidence: 99%